Modified carboxymethyl chitosan-based conductive composite material modified electrode and preparation method and application thereof
By modifying the electrode with a carboxymethyl chitosan-based conductive composite, the problem of high detection cost, long time, and difficulty in detecting multiple heavy metal ions in the prior art is solved, and the high sensitivity and simultaneous detection of cadmium, lead and copper ions is achieved, which is suitable for actual water sample analysis.
Patent Information
- Application Number
- CN202411682762.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The existing heavy metal ion detection technology is costly, time-consuming and difficult to achieve high sensitivity detection of a variety of heavy metal ions.
The electrode was modified with a modified carboxymethyl chitosan-based conductive composite material, and the electrochemical sensor for heavy metal ion detection was prepared by L-methionine graft modified carboxymethyl chitosan composite with polypyrrole and multi-walled carbon nanotubes.
Simultaneous high sensitivity detection of cadmium, lead and copper ions was achieved, with a linear determination range of 0.01-5 μmol/L, and detection limits were 5, 4, and 6 nmol/L, respectively, and good recovery and stability were shown in actual river water samples.
Smart Images

Figure CN119534577A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heavy metal detection sensors, and in particular to a modified carboxymethyl chitosan-based conductive composite material modified electrode and a preparation method and application thereof. Background Art
[0002] Heavy metal ions (HMIs) refer to ions corresponding to metal elements with a density greater than 4.5 grams per cubic centimeter. They can gradually accumulate in the human body through the food chain, causing various adverse effects on human health. For example, Cd 2+ Once absorbed by the human body, it is difficult to eliminate and can cause lesions in the kidneys, lungs, liver, bones and reproductive organs. 2+ After being ingested by the human body, it can cause multiple damages to the human nervous system, digestive system, urinary system, blood circulation system, etc. 2+ When the intake exceeds the normal level required by the body, it will cause serious diseases such as gastrointestinal bleeding, hematuria, hemolysis, methemoglobinemia, liver poisoning, acute renal failure, etc. In order to avoid the harm of heavy metal ions to the environment and human body, it is of great significance to develop high-sensitivity and high-reliability heavy metal ion detection technology. Considering that heavy metal ions in pollutants usually coexist in multiple forms, it is necessary to develop a simultaneous detection technology for multiple heavy metal ions.
[0003] Methods commonly used to detect HMIs include atomic absorption spectroscopy, inductively coupled plasma mass spectrometry, inductively coupled plasma atomic emission spectrometry, fluorescence determination, and colorimetry, among others. However, these technical instruments and equipment are costly, require highly skilled professional manpower, and are time-consuming, which limits their application in the simultaneous detection of HMIs. Therefore, there is an urgent need to develop a portable, low-cost, and high-precision in situ analytical method for sensitive and selective monitoring of multiple HMIs in water resources. In recent years, anodic stripping voltammetry (ASV) has attracted widespread attention in HMIs monitoring due to its fast response, low cost, simplicity, portability, and high reliability. The performance of ASV mainly depends on the working electrode, and the modified electrode material is the core component of the electrochemical method, so the selection of a suitable electrode modification material is crucial. Summary of the invention
[0004] In view of this, the object of the present invention is to provide a modified carboxymethyl chitosan-based conductive composite material modified electrode and a preparation method and application thereof.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] One of the technical solutions of the present invention is a method for preparing a modified carboxymethyl chitosan-based conductive composite material modified electrode, comprising the following steps:
[0007] After dissolving the carboxymethyl chitosan, an activator is added to activate it, and then L-methionine is added to carry out a coupling reaction to obtain a carboxymethyl chitosan derivative grafted with L-methionine;
[0008] Dispersing the L-methionine grafted modified carboxymethyl chitosan derivative, polypyrrole and multi-walled carbon nanotubes in a solvent to obtain a dispersion;
[0009] The dispersion is coated on the surface of the base electrode and dried to obtain the modified carboxymethyl chitosan-based conductive composite material modified electrode.
[0010] The second technical solution of the present invention is a modified carboxymethyl chitosan-based conductive composite material modified electrode prepared by the above preparation method.
[0011] The third technical solution of the present invention is an electrochemical sensor, wherein the working electrode is the modified carboxymethyl chitosan-based conductive composite material modified electrode.
[0012] A fourth technical solution of the present invention is an application of the modified carboxymethyl chitosan-based conductive composite material modified electrode or the electrochemical sensor in the detection of heavy metal ions; the heavy metal ions are at least one of cadmium ions, lead ions and copper ions.
[0013] A fifth technical solution of the present invention is a method for detecting heavy metal ions, which comprises assembling the modified carboxymethyl chitosan-based conductive composite material modified electrode, a reference electrode and a counter electrode into a three-electrode system, and placing the system in a buffer solution containing heavy metal ions for SWASV electrochemical testing.
[0014] The present invention discloses the following technical effects:
[0015] The present invention adopts L-methionine as a grafting group to graft-modify carboxymethyl chitosan, and then composites it with polypyrrole and multi-walled carbon nanotubes to prepare a modified carboxymethyl chitosan-based conductive composite material, and constructs an electrochemical sensor for simultaneously determining cadmium, lead, and copper ions based on the conductive composite material modified electrode. The conductivity of the composite material is enhanced by introducing polypyrrole and carbon nanotubes, and the introduction of carbon nanotubes is conducive to increasing the specific surface area of the composite material. In addition, sulfur is introduced into the L-methionine-modified carboxymethyl chitosan, which improves the chelating ability of the composite material to heavy metal ions, and the chelating ability of Cd is achieved under the synergistic effect of the three substrates. 2+ , Pb 2+ and Cu 2+ Under the optimal experimental conditions, the constructed electrochemical sensor can detect Cd 2+, Pb 2+ and Cu 2+ The linear determination range is 0.01-5μmol / L, and the detection limits are 5, 4, and 6nmol / L, respectively. In addition, the sensor has good stability and selectivity, and can be used for the recovery of Cd by adding spikes to actual river water samples. 2+ , Pb 2+ and Cu 2+ The recovery rates of the three were between 96.36% and 103.35%, indicating that this sensor is suitable for Cd in actual water samples. 2+ , Pb 2+ and Cu 2+ Simultaneous electrochemical analysis monitoring. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0017] Figure 1 This is the schematic diagram of L-methionine grafted onto carboxymethyl chitosan;
[0018] Figure 2 The infrared spectra of CMCS and CMCS-Met in the effect verification example;
[0019] Figure 3 CV curves of bare GCE and M-GCE in the effect verification example;
[0020] Figure 4 The EIS curves of bare GCE and M-GCE in the effect verification example;
[0021] Figure 5 In the effect verification example, bare electrode GCE simultaneously measures Cd 2+ , Pb 2+ and Cu 2+ SWASV diagram;
[0022] Figure 6 M-GCE simultaneous determination of Cd in the effect verification example 2+ , Pb 2+ and Cu 2+ SWASV diagram;
[0023] Figure 7 To optimize the amount of conductive composite material used in the effect verification example;
[0024] Figure 8To optimize the enrichment potential in the effect verification example;
[0025] Fig. 9 To optimize the enrichment time in the effect verification example;
[0026] Fig.10 To optimize the pH of the buffer solution containing heavy metal ions in the effect verification example;
[0027] Fig.11 To verify the effect of the SWASV method in the example, the SWASV method was used to simultaneously determine different concentrations of Cd. 2+ , Pb 2+ and Cu 2+ Graph of
[0028] Fig.12 To verify the effect of the detection of Cd 2+ The standard curve of
[0029] Fig.13 To test Pb in the effect verification example 2+ The standard curve of
[0030] Fig.14 To verify the effect, Cu 2+ The standard curve of DETAILED DESCRIPTION
[0031] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0032] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0033] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0034] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.
[0035] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0036] The first aspect of the present invention provides a method for preparing a modified carboxymethyl chitosan-based conductive composite material modified electrode, comprising the following steps:
[0037] After dissolving the carboxymethyl chitosan, an activator is added for activation, and then L-methionine is added for coupling reaction to obtain a carboxymethyl chitosan derivative grafted with L-methionine (referred to as CMCS-Met);
[0038] Dispersing the L-methionine grafted modified carboxymethyl chitosan derivative, polypyrrole and multi-walled carbon nanotubes in a solvent to obtain a dispersion;
[0039] The dispersion is coated on the surface of the base electrode and dried to obtain the modified carboxymethyl chitosan-based conductive composite material modified electrode (denoted as CMCS-Met-PPy-CNT / GCE modified electrode, abbreviated as M-GCE).
[0040] In some embodiments of the present invention, the solvent for dissolving carboxymethyl chitosan is water.
[0041] In some embodiments of the present invention, the activators are EDC and NHS; the mass ratio of chitosan, EDC, NHS and L-methionine is (0.8-1.5):(0.7-1.2):(0.5-0.8):(0.6-0.9), preferably 1:0.9:0.6:0.7.
[0042] In some embodiments of the present invention, the activation parameters are set as: stirring at room temperature for 20-40 minutes, preferably stirring at room temperature for 30 minutes; the coupling reaction parameters are set as: reacting at room temperature for 10-18 hours; when performing the coupling reaction, the pH value of the reaction system is 6.5-7.5. The present invention uses a dilute alkali solution (e.g., sodium hydroxide solution) to adjust the pH value to be close to neutral, so as to better perform the coupling reaction and graft L-methionine onto carboxymethyl chitosan.
[0043] In some embodiments of the present invention, after the coupling reaction is completed, the product is dialyzed in ultrapure water for two days and then freeze-dried.
[0044] In some embodiments of the present invention, the method for preparing the dispersion is specifically as follows: weigh CMCS-Met, polypyrrole and multi-walled carbon nanotubes, dissolve them in a solvent (preferably DMF), respectively, then ultrasonically disperse them into suspensions, and finally mix the three suspensions evenly.
[0045] In some embodiments of the present invention, the mass volume ratio of the L-methionine grafted modified carboxymethyl chitosan derivative, polypyrrole, multi-walled carbon nanotubes and solvent is 2-4 mg:2-4 mg:2-4 mg:3 mL, preferably 3 mg:3 mg:3 mg:3 mL.
[0046] In some embodiments of the present invention, before coating the dispersion on the surface of the substrate electrode, the substrate electrode is polished on 0.3 μm and 0.05 μm Al2O3 pastes in sequence, and then ultrasonically cleaned in a mixed solution of nitric acid, anhydrous ethanol and water in a volume ratio of 1:1:1, and blown dry with nitrogen.
[0047] In some embodiments of the present invention, the substrate electrode is a glassy carbon electrode (GCE). In the present invention, the glassy carbon electrode used is in the shape of a cylinder, and its bottom surface (i.e., the active surface in contact with the electrolyte) is a circle with a diameter of 3 mm.
[0048] In some embodiments of the present invention, when the dispersion is applied to the surface of the substrate electrode, the amount of the dispersion is set to: 2 The amount used for the active working area of the substrate electrode is 3-6 μL. 7.07mm 2 The area of the active working area of the substrate electrode is calculated based on the bottom surface of the substrate electrode (i.e., the active surface in contact with the electrolyte) being a circle with a diameter of 3 mm. The present invention does not make any special requirements on the method of coating the dispersion on the surface of the substrate electrode, and conventional technical means of those skilled in the art can be used, such as drip coating.
[0049] In some embodiments of the present invention, the drying method is drying under infrared light.
[0050] The second aspect of the present invention provides a modified carboxymethyl chitosan-based conductive composite material modified electrode prepared by the preparation method described in the above technical solution.
[0051] The third aspect of the present invention provides an electrochemical sensor, wherein the working electrode is the modified carboxymethyl chitosan-based conductive composite material modified electrode.
[0052] The fourth aspect of the present invention provides an application of the above-mentioned modified carboxymethyl chitosan-based conductive composite material modified electrode or the above-mentioned electrochemical sensor in the detection of heavy metal ions; the heavy metal ions are at least one of cadmium ions, lead ions and copper ions.
[0053] The fifth aspect of the present invention provides a method for detecting heavy metal ions. After the modified carboxymethyl chitosan-based conductive composite material modified electrode is assembled into a three-electrode system with a reference electrode and a counter electrode, it is placed in a buffer solution containing heavy metal ions for SWASV electrochemical testing; the heavy metal ions are at least one of cadmium ions, lead ions and copper ions.
[0054] In some embodiments of the present invention, the pH value of the buffer solution containing heavy metal ions is 4-6.5; the parameters of the SWASV electrochemical test are set as: the enrichment voltage is -0.9V to -1.3V, and the enrichment time is 250s.
[0055] In some embodiments of the present invention, the parameters of the SWASV electrochemical test are set as follows: the enrichment voltage is -1.0V to -1.2V, and the enrichment time is 250s.
[0056] In some embodiments of the present invention, the parameters of the SWASV electrochemical test are set as follows: the enrichment voltage is -1.2 V, and the enrichment time is 250 s.
[0057] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0058] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art.
[0059] Instruments and reagents:
[0060] O-carboxymethyl chitosan (CMCS), carboxylation degree ≥ 80%, molecular weight 150,000-800,000, Shanghai Yuanye Biotechnology Co., Ltd.; L-methionine (Met), polypyrrole (PPy), acetic acid, sodium acetate, DMF Shanghai McLean Biochemical Technology Co., Ltd.; multi-walled carbon nanotubes (MWCNT) were purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd. Cadmium nitrate standard solution (1 mg / mL), lead nitrate standard solution (0.1 mol / L), copper nitrate standard solution (0.1 mol / L) were purchased from Beijing North Weiye Metrology Technology Research Institute. All drugs were analytically pure and were not further treated before use. The water used in this experiment was deionized water, provided by Ecopur A2S-05-CE.
[0061] Infrared spectrometer (FT-IR), Spectrum 3, PerkinElmer, USA; electrochemical workstation, CHI660E, Shanghai Chenhua Instrument Co., Ltd. Glassy carbon electrode (3 mm diameter), silver-silver chloride electrode and platinum sheet electrode were purchased from Shanghai Yueci Electronic Technology Co., Ltd.
[0062] Example 1
[0063] The preparation steps of the modified carboxymethyl chitosan-based conductive composite material modified electrode are as follows:
[0064] Step 1. Preparation of modified chitosan
[0065] 1 g of carboxymethyl chitosan was weighed and dissolved in 100 mL of water, followed by the addition of 0.9 g of EDC and 0.6 g of NHS, and activated for 30 min under stirring at room temperature, followed by the addition of 0.7 g of L-methionine, followed by the adjustment of the system pH to 6.5 with a dilute alkali solution, and then reacted for 12 hours. The product was then dialyzed in ultrapure water for two days, and finally freeze-dried to obtain a carboxymethyl chitosan derivative grafted with L-methionine, recorded as CMCS-Met.
[0066] Step 2. Preparation of modified carboxymethyl chitosan-based conductive composite modified electrode
[0067] Electrode pretreatment: The glassy carbon electrode (GCE) was polished on 0.3 μm and 0.05 μm Al2O3 pastes in turn, and then ultrasonically cleaned in a mixed solution of nitric acid, anhydrous ethanol and water in a volume ratio of 1:1:1, and dried with nitrogen for later use.
[0068] Preparation of modified carboxymethyl chitosan-based conductive composite modified electrode: 3 mg CMCS-Met, 3 mg polypyrrole, and 3 mg multi-walled carbon nanotubes were weighed and dissolved in 1 mL DMF, and then ultrasonically dispersed into suspensions, and finally the three suspensions were mixed to obtain a composite mixed solution. Subsequently, 4.5 uL of the composite mixed solution was added dropwise to the treated GCE surface, and then dried under infrared light to obtain a CMCS-Met-PPy-CNT / GCE modified electrode (modified GCE), abbreviated as M-GCE.
[0069] Effect verification example
[0070] 1. Characterization of Materials
[0071] The schematic diagram of L-methionine grafting carboxymethyl chitosan is shown in Figure 1 As shown, under the synergistic effect of EDC and NHS, the amino group on Met is coupled to the carboxyl group on CMCS. In order to prove the successful grafting of the material, the present invention uses infrared spectroscopy to characterize the grafted product. The test results are shown in Figure 2 shown. Figure 2 Curve a in the middle is the infrared spectrum of CMCS, 1587cm -1 The wave number is the absorption band of the symmetric stretching vibration of carboxyl and the bending vibration of NH, 1417 cm -1 The wave number near the asymmetric stretching vibration absorption band of carboxyl is 1311cm -1Near the wave number is the CN stretching vibration absorption band. Figure 2 Curve b is the infrared spectrum of CMCS-Met. Compared with the spectrum of CMCS, the infrared spectrum of CMCS-Met is -1 The characteristic absorption band of Met appeared nearby, 1640cm -1 and 1575cm -1 The wave number near is the stretching vibration absorption band of C=O, and the asymmetric stretching vibration of carboxyl group is from 1417cm -1 Shift to lower wavenumbers at 1402 cm -1 , and the stretching vibration of CN from 1311cm -1 Move to higher wave number 1322cm -1 , indicating that after L-methionine was grafted onto carboxymethyl chitosan, the carboxyl group on Met and the amino group on CMCS underwent electrostatic interaction. The above results indicate that the L-methionine-modified carboxymethyl chitosan derivative was successfully synthesized.
[0072] 2. Electrochemical testing
[0073] The three-electrode system was placed in 10mL 0.1mol / LHAc-NaAc buffer solution. After the system was stable, heavy metal ion cadmium, lead, and copper standard samples were added. They were first enriched at a certain potential, and then electrochemically tested by square wave anodic stripping voltammetry (SWASV). Electrochemical test parameters and conditions: Cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) were performed at 5mmol / L [Fe(CN)6] 3- / 4- The test was carried out in an electrolyte solution containing 0.1 mol / L KCl to enhance the conductivity of the electrolyte. The CV scan range was -0.4 to 0.6 V, and the scan rate was 100 mV / s. The EIS test frequency range was 0.1 Hz to 10 kHz, the amplitude was 50 mV, and the bias voltage was the open circuit voltage. SWASV test parameters: scan range was -1.0 to 0.2 V, amplitude was 25 mV / s, enrichment potential was -1.2 V, and enrichment time was 250 s.
[0074] 2.1 Electrochemical characterization of different electrodes: The present invention uses two electrochemical test methods, cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS), to study the modification of the conductive composite material on the GCE surface. The test results are as follows: Figure 3 and Figure 4 shown.
[0075] The CV results of GCE and M-GCE are as follows: Figure 3 As shown in curves a and b, it can be seen that both the bare GCE and M-GCE CV graphs have a pair of obvious [Fe(CN)6] 3- / 4-However, in the CV curve of M-GCE, [Fe(CN)6] 3- / 4- The redox peaks of the modified GCE are wider, that is, the oxidation peak current value is larger and the reduction peak current value is smaller, indicating that the conductivity of the modified GCE becomes stronger, which is conducive to the redox couple approaching the electrode surface and promoting the transfer of electrons on the electrode surface.
[0076] In the Nyquist plot of electrochemical impedance spectroscopy (EIS), the semicircle observed at higher frequencies corresponds to the limiting process of charge transfer, and the diameter of the semicircle reflects the electron transfer impedance value (Rct) of the electrode surface. The EIS results of GCE and M-GCE are shown in Figure 2. Figure 4 As shown in curve a and curve b, it can be seen from the figure that the interfacial charge transfer resistance Rct of GCE is 211Ω, while the interfacial charge transfer resistance Rct of M-GCE is 49Ω. It can be seen that compared with bare GCE, the EIS graph of M-GCE shows a smaller semicircle, which indicates that after the conductive composite material is modified, the charge transfer resistance on the electrode surface is reduced. This is because multi-walled carbon nanotubes and polypyrrole have strong conductivity, which is conducive to the transfer of redox couples on the modified electrode surface. It can be seen that the EIS test results are consistent with the CV test results, both of which prove that the M-GCE modified electrode is successfully constructed.
[0077] 3. Feasibility study of modified electrodes
[0078] Square wave anodic stripping voltammetry (SWASV) includes two electrochemical processes, namely, enrichment and stripping. It is a highly sensitive electrochemical method for determining trace metal ions. Therefore, the present invention selects SWASV method for simultaneous determination of Cd in water. 2+ , Pb 2 + and Cu 2+ The electrochemical response of bare GCE and M-GCE to heavy metal ions was compared to evaluate the binding capacity of M-GCE to heavy metal ions. The SWASV test results of bare GCE and M-GCE to three heavy metal ions are shown in Figure 2. Figure 5 and Figure 6 shown.
[0079] from Figure 5 It is concluded that Cd 2+ , Pb 2+ and Cu 2+The dissolution peak potentials of the three metal ions (test concentration of 1 μM) on the bare GCE electrode are -0.78V, -0.48V and -0.10V, and the dissolution peak current ΔI (peak current minus baseline current) are 1.05μA, 1.56μA and 1.34μA, respectively. The dissolution peak potentials of the three metal ions on the M-GCE electrode are -0.79V, -0.55V and -0.04V, and the dissolution peak current ΔI are 3.88μA, 4.48μA and 3.85μA, respectively. It can be seen that the peak current has been significantly improved, increasing by 2.83μA, 2.92μA and 2.51μA, respectively. In addition, compared with the baseline current value of 3.92μA of GCE, the baseline current value of M-GCE is 141.26μA, which is significantly higher than the baseline current of GCE, which further confirms that the M-GCE surface modified with conductive composite materials has better conductivity. Another obvious test result is that the dissolution peaks of the three heavy metal ions on M-GCE are three sharp peaks, while on GCE they are broad peaks, which also shows that M-GCE has a strong effect on Cd 2+ , Pb 2+ and Cu 2+ The three heavy metal ions have better discrimination, which may be attributed to the fact that the conductive composite material has active groups such as amino, carboxyl, sulfur, and π bonds, which play a key role in the enrichment and dissolution of heavy metal ions. 2+ , Pb 2+ and Cu 2+ The electrochemical responses of the three heavy metal ions were effectively improved, and the M-GCE electrode can be used as a sensing platform for the simultaneous determination of the three.
[0080] 4. Optimization of the amount of conductive composite material applied
[0081] The amount of modified chitosan-based conductive composite material directly affects the deposition of metal ions on the electrode surface, and further affects the electrochemical test results. Therefore, the present invention first optimizes the drop coating amount of modified chitosan-based conductive composite material on GCE. The effects of 3, 3.5, 4, 4.5, 5 and 6 μL of material modification on the electrochemical detection of heavy metal ions are studied. 2+ , Pb 2+ and Cu 2+ The detection concentration of the three is 1μM, and the test results are as follows Figure 7As shown. It can be seen that when the modification amount of the composite material increases from 3 μL to 4.5 μL, the electrochemical response currents of the three metal ions gradually increase and reach a maximum value. On the contrary, when the modification amount continues to increase, the electrochemical response currents of the three do not increase but decrease. This is because when the modification amount is less than 4.5 μL, the composite material is not completely covered with the electrode surface and cannot provide enough active sites. Therefore, when the modification amount of the material gradually increases from 3 μL to 4.5 μL, the electrochemical response currents of the three gradually increase. When the modification amount of the material continues to increase, the material is stacked on the electrode surface, causing the material to easily fall off from the electrode surface, and too much modification material may also hinder electron transmission, so excessive modification will cause the electrochemical response current to decrease. Therefore, the present invention selects 4.5 μL as the optimal composite material drop coating amount.
[0082] 5. Optimization of Enrichment Potential
[0083] The enrichment potential is another key factor affecting the accuracy of electrochemical detection. The present invention discusses the effect of enrichment potential from -0.9V to -1.3V on the accuracy of Cd 2+ , Pb 2+ and Cu 2+ The test concentration of the three was 1 μM. The experimental results are as follows Figure 8 As shown. It can be seen that when the enrichment potential is within the range of -0.9V to -1.3V, when the enrichment potential gradually becomes negative, the dissolution peak current values of the three first increase and then decrease, reaching a maximum value at -1.2V. When the potential continues to increase negatively to -1.3V, the dissolution peak current value decreases. This is because when the enrichment potential increases negatively from -0.9V to -1.2V, as the potential increases negatively, it is more conducive to the electrodeposition of metal ions, so the dissolution peak current of metal ions is also greater. When the enrichment potential continues to shift negatively, a hydrogen evolution reaction will occur on the surface of the modified electrode at this time, hindering the electrochemical deposition of metal ions, so the dissolution peak current is correspondingly reduced. Therefore, the present invention selects -1.2V as the best electrochemical enrichment potential.
[0084] 6. Optimization of enrichment time
[0085] The principle of the SWASV electrochemical test method is to electrochemically reduce metal ions to the electrode surface first and then electrochemically dissolve them. Therefore, the choice of enrichment time in this process will directly affect the test results. 2+ , Pb 2+ and Cu 2+ The electrochemical tests of the three showed that as the electrochemical deposition time increased, the peak current values of the three gradually increased. The test results are as follows Fig. 9As shown, the maximum current value was obtained at 250s, and then tended to be flat, indicating that 250s was sufficient for the electrochemical deposition of the three, so 250s was selected as the optimal electrochemical enrichment time.
[0086] 7. Optimization of pH of electrochemical test solution
[0087] Because the stability of heavy metal ions in solutions with different pH values is different, the pH of the test system also affects the electrochemical test results. The test buffer solution selected in the present invention is a 0.1 mol / L HAc-NaAc buffer solution. The effects of the test buffer solutions with pH values of 4, 4.5, 5, 5.5, 6, and 6.5 on the SWASV test of 1 μM Cd 2+ , Pb 2+ and Cu 2+ The test results are as follows: Fig.10 As shown, it can be seen that when the pH of the test system increases from 4.0 to 5.5, the dissolution current values of the three gradually increase. When the pH of the test solution continues to increase, the dissolution current value decreases slightly. Therefore, the present invention selects the pH of the test solution to be 5.5.
[0088] 8. Establishment of standard curve and detection limit
[0089] A three-electrode test system was used, with M-GCE as the working electrode, Ag / AgCI as the reference electrode, and a platinum wire electrode as the counter electrode. Under the above optimized test conditions, the SWASV electrochemical test technology was used to measure the Cd 2+ , Pb 2+ and Cu 2+ Three heavy metal ions were electrochemically tested simultaneously. The test results are as follows: Fig.11 As shown, the concentrations corresponding to curves a to f are 0, 0.01, 0.1, 1, 2, and 5 μmol / L. As can be seen from the figure, with the increase of the test concentration of heavy metal ions, the electrochemical response current values of the three increase. In the range of 0.01-5 μmol / L, the dissolution peak current values of the three show a good linear relationship with their concentrations. The linear regression equations are ΔI = 2.76 × C (Cd 2+ )+1.08, linear correlation coefficient R 2 =0.998, see Fig.12 ; ΔI=3.10×C(Pb 2+ )+1.03, linear correlation coefficient R 2 =0.998, see Fig.13 ; ΔI=2.07×C(Cu 2+ )+1.83, linear correlation coefficient R 2 =0.998, see Fig.14The detection limit is calculated as follows: the blank sample is measured 10 times in parallel to obtain the standard deviation (s), and the 3 times value of the standard deviation s is compared with the slope k of the standard curve (LOD = 3s / k) to obtain Cd 2+ , Pb 2+ and Cu 2+ The detection limits of the three heavy metal ions of the present invention meet the detection limits of the World Health Organization [WHO.Guidelines for drinking-water quality, World Health Organization, 2004, vol. 1.] and the national drinking water standard [Sanitary Standard for Drinking Water, GB 5749-2006, National Standard of the People's Republic of China] for Cd in water. 2+ , Pb 2+ and Cu 2+ testing requirements.
[0090] 9. Study on the stability and selectivity of electrodes
[0091] In order to study the stability of the M-GCE electrode, the electrode modified with the composite material was placed in a refrigerator at 4 °C for one month, and then the SWASV method was used to simultaneously determine 1 μM Cd 2+ , Pb 2+ and Cu 2+ Compared with the test results of the newly prepared M-GCE, the three heavy metal ions, Cd 2+ The peak current value of the dissolution is 92.36% of the new electrode current. 2+ The peak current value of the dissolution is 93.45% of the new electrode current. 2+ The dissolution peak current value is 93.69% of the new electrode current, indicating that the activity of this modified electrode is well maintained and can be stably stored in a short period of time.
[0092] The selectivity of M-GCE was investigated by testing the interference of coexisting ions. Specifically, in order to investigate the selectivity of the electrode, in the presence of 10 μM Ca 2+ , K + Mg 2+ , Fe 2+ 、Zn 2+ 、SO4 2- , Cl - 、NO3 - Under plasma conditions, 1 μM Cd 2 + , Pb 2+ and Cu 2+The SWASV test was performed. The SWASV test results showed that even in the presence of 10 times the concentration of the above interfering ions, the dissolution peak current responses of the three were all above 92.54% of the current when there were no interfering ions, that is, the coexisting interfering ions had little effect on the target ion response current, indicating that this sensor has good selectivity.
[0093] 10. Actual sample analysis
[0094] Water from a freshwater river was taken, filtered through a 0.45μm filter membrane, and diluted 5 times with 0.1M HAc-NaAc solution. A spike recovery experiment was carried out under the optimal test conditions. Each experiment was parallel measured 3 times and the average value was taken. The test results are shown in Table 1. The spike recovery rate was between 96.36% and 103.35%, and the coefficient of variation RSD was between 2.61% and 3.41%, indicating that the spike recovery rate of the sensor is good and can be used for heavy metal ion analysis of actual water samples.
[0095] Table 1 Spike recovery test results
[0096]
[0097] In summary, the present invention synthesizes L-methionine-modified carboxymethyl chitosan derivatives by chemical coupling method, and composites them with polypyrrole and multi-walled carbon nanotubes to prepare a conductive composite material, and then modifies the conductive composite material on the surface of a glassy carbon electrode to construct an electrochemical sensor for the simultaneous determination of cadmium, lead, and copper ions. The glassy carbon electrode modified with the conductive composite material improves the discrimination of the three heavy metal ions. In the concentration range of 0.01-5μM, the constructed electrochemical sensor has a good linear correlation for the three heavy metal ions. The spike recovery results show that the sensor is suitable for the simultaneous electrochemical monitoring of cadmium, lead, and copper ions in water.
[0098] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a modified carboxymethyl chitosan-based conductive composite material modified electrode, characterized in that: The following steps are involved: After dissolving the carboxymethyl chitosan, an activator is added to activate it, and then L-methionine is added to carry out a coupling reaction to obtain a carboxymethyl chitosan derivative grafted with L-methionine; Dispersing the L-methionine grafted modified carboxymethyl chitosan derivative, polypyrrole and multi-walled carbon nanotubes in a solvent to obtain a dispersion; The dispersion is coated on the surface of the base electrode and dried to obtain the modified carboxymethyl chitosan-based conductive composite material modified electrode.
2. The method for preparing a modified carboxymethyl chitosan-based conductive composite material modified electrode according to claim 1, characterized in that: The activators are EDC and NHS; the mass ratio of the carboxymethyl chitosan, EDC, NHS and L-methionine is (0.8-1.5):(0.7-1.2):(0.5-0.8):(0.6-0.9).
3. The method for preparing a modified carboxymethyl chitosan-based conductive composite material modified electrode according to claim 1, characterized in that: The activation parameters are set as: stirring at room temperature for 20-40 minutes; the coupling reaction parameters are set as: reaction at room temperature for 10-18 hours; when performing the coupling reaction, the pH value of the reaction system is 6.5-7.
5.
4. The method for preparing a modified carboxymethyl chitosan-based conductive composite material modified electrode according to claim 1, characterized in that: The mass volume ratio of the L-methionine grafted modified carboxymethyl chitosan derivative, polypyrrole, multi-walled carbon nanotubes and solvent is 2-4 mg: 2-4 mg: 2-4 mg: 3 mL.
5. The method for preparing a modified carboxymethyl chitosan-based conductive composite material modified electrode according to claim 1, characterized in that: When the dispersion is applied to the surface of the substrate electrode, the amount of the dispersion is set to: 2 The amount used in the active working area of the substrate electrode is 3-6 μL.
6. A modified carboxymethyl chitosan-based conductive composite material modified electrode prepared by the preparation method according to any one of claims 1 to 5.
7. An electrochemical sensor, characterized in that The working electrode is the modified carboxymethyl chitosan-based conductive composite material modified electrode as described in claim 6.
8. Use of the modified carboxymethyl chitosan-based conductive composite material modified electrode according to claim 6 or the electrochemical sensor according to claim 7 in the detection of heavy metal ions; the heavy metal ions are at least one of cadmium ions, lead ions and copper ions.
9. A method for detecting heavy metal ions, characterized in that: After assembling the modified carboxymethyl chitosan-based conductive composite material modified electrode described in claim 7, a reference electrode and a counter electrode into a three-electrode system, the system is placed in a buffer solution containing heavy metal ions for SWASV electrochemical testing.
10. The method for detecting heavy metal ions according to claim 9, characterized in that: The pH value of the buffer solution containing heavy metal ions is 4-6.5; the parameters of the SWASV electrochemical test are set as follows: the enrichment voltage is -0.9V to -1.3V, and the enrichment time is 250s.
Citation Information
Patent Citations
Simultaneous detection method and sensor of L-tyrosine and based on composite membrane modified electrode
CN110082416A
Preparation method and application of carboxymethyl chitosan-based hydrogel modified electrode
CN115753933A
Carbon nanotube structure-selective separation and surface fixation
CN1922106A
Biosensor for continuous monitoring of metabolites and proteins and methods of manufacture thereof
US20100116691A1
Cited By
Method for detecting heavy metals in water
CN120044089A